Cointegration of 'MIBOR' with rupee-dollar and rupee-yen exchange rates: estimating volatility spill-overs and asymmetry. (12th December 2022) - Shukla, Upendra Nath; Tandon, Neelam; Tandon, Deepak; Gupta, Hemendra
Mumbai Interbank Offer Rate (MIBOR) plays a significant role in the Indian interbank market and its role would be more imperative in India as LIBOR is expected to be ceased by 2021. This paper has a purpose to understand the movement and volatility of MIBOR by exploring any cointegration of MIBOR with exchange rates of major currencies like - US dollar, Japanese yen, euro and pound sterling, to derive a model gauging volatility spill-overs and asymmetry of MIBOR. Based on the daily data from 01.01.19 to 21.01.21 VECM and E-Garch model is applied. MIBOR is found to be cointegrated with exchange rates of dollar and yen with error correction being done by the rupee-yen exchange rates. Volatility spill-overs were significant with previous error lag with no asymmetry due to any negative news. Findings have great implications to manage interest rates and liquidity in Indian interbank and money markets.